2016
DOI: 10.18006/2016.4(4).414.420
|View full text |Cite
|
Sign up to set email alerts
|

Influence of organic and mineral fertilizers on the antioxidants and total phenolic compounds level in tomato (Solanum lycopersicum) var. mongal F1

Abstract: The availability of secondary metabolites in various plant parts can be influenced qualitatively and quantitatively by managing ecological factors or farming practices. Purpose of this study was to determine the impact of organic and mineral fertilization on the content of phenolic compounds and antioxidant activity in fruit of the tomato Mongal F1 variety. Experimentation was carried out in a randomized block factorial design. Results of study revealed that plant treated by organic fertilizers have 16.36± 0.0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
7
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 40 publications
2
7
1
Order By: Relevance
“…The values obtained are lower than those of Rotino et al [22] with values ranging from 49.11 to 69.85 mg / 100 g DM on four tomato genotypes. They are similar to those obtained by Georgé et al [21] and Tudor-Radu et al [23] with respective values of 17.4 and 9.26 to 33.40 mg / 100g MS. Like the lycopene content, the β-carotene content may also depend on several factors such as variety, degree of maturity and agronomic conditions [13,25].…”
Section: β-Carotene Content (Mg / 100 G Dm)supporting
confidence: 91%
See 2 more Smart Citations
“…The values obtained are lower than those of Rotino et al [22] with values ranging from 49.11 to 69.85 mg / 100 g DM on four tomato genotypes. They are similar to those obtained by Georgé et al [21] and Tudor-Radu et al [23] with respective values of 17.4 and 9.26 to 33.40 mg / 100g MS. Like the lycopene content, the β-carotene content may also depend on several factors such as variety, degree of maturity and agronomic conditions [13,25].…”
Section: β-Carotene Content (Mg / 100 G Dm)supporting
confidence: 91%
“…The values found in the present in the present study are below than those reported by Tudor-Radu et al [23] which ranged from 29911.50 to 42874.01mg of GEA / 100g DM. On the other hand, they are lower than the values of George et al [21] on red tomato and those of Sahlin et al [20] on two varieties (Excell, Aranca) with respective values of 268 mg and 354.83 to 438.6 mg GEA / 100 g DM. Also, they are above those obtained by Seremé et al [26] for Burkina Faso tomato Mongal F1 with values of 157.33 to 193.47 mg GEA / 100 g DM.…”
Section: Total Polyphenol Content (Mg Gea / 100 G Dm)contrasting
confidence: 60%
See 1 more Smart Citation
“…The smallest total polyphenols content (60 µM gallic acid/g) was found in exclusive mineral fertilization case (M2), with the highest mineral nitrogen dose applied in one step (150 kg/ha). Sereme et al (2016) highlighted also that organic fertilisation with fermented manure (livestock) increase the phenolics compounds content of plants comparatively with mineral N P K fertilizers.…”
Section: Resultsmentioning
confidence: 99%
“…The same source states that, soils rich in humus with high biological activity can positively modify the concentration and the combination of antioxidants in harvested fruits and vegetables, compared to soils that are regularly fumigated and extensively chemical fertilized, and which have a generally lower bioactivity [41]. It could be argued that the ability of organic farming practices to increase the antioxidant content of fruits and vegetables would come from the use of organic fertilizers and pesticides, which are very rich in organic and probably other agro-ecological parameters could explain the increase of antioxidant content in organic farming according to many authors, Dakéné, et al [42]; Sereme, et al [43]; Dabire, et al [44].…”
Section: Cultural Practices and Influence On The Antioxidant Content mentioning
confidence: 99%